Electroconvulsive therapy in a patient with hypertrophic cardiomyopathy: A case report. Issue 9 (5th September 2022) - Kufner, Marco; Nothdurfter, Caroline; Steffling, Dagmar; Baessler, Andrea; Maier, Lars S.; Qamar, Yasmin
Abstract: The use of electroconvulsive therapy (ECT) in patients with underlying cardiac disease like hypertrophic cardiomyopathy (HCM) remains without satisfactory clinical guidelines. We provide a case report of successful application of ECT in a 43‐year‐old patient with bipolar disorder and comorbid HCM, including detailed diagnostic information and outlining key clinical considerations. Abstract : Suggested prerequisites for ECT application in HCM patients: (1) low risk‐SCD score (no late gadolinium enhancement, no LVOT obstruction). (2) No arrhythmia in holter ECG. (3) Bedside defibrillation standby during ECT. (4) Beta blocker pretreatment.